Evaluation of Aseptic Actions of Pharmaceutical Technical Staff in the Process of Reconstitution and Storage of Antibiotic Injection in the Inpatient Room of UNS Hospital - Eka Rahma Noviyanti; Lusia Murtisiwi (Jurnal Farmasi (Journal of Pharmacy), 2022)
aseptic dispensing, reconstitution and storage of antibiotic injection